Experimental investigation of the effect of addition of different activators to aqueous solution of potassium carbonate: Absorption rate and solubility. (February 2016) - Ramazani, R.; Mazinani, S.; Jahanmiri, A.; Van der Bruggen, B.
Highlights: Various activators were suggested to enhance the performance of K2 CO3 solution. TEPA, PZEA, MEA, PZ and Boric Acid were considered as activators. Different molar ratios of promoter to K2 CO3 were investigated. Highest absorption rate and CO2 solubility achieved for the TEPA + K2 CO3 solution. Abstract: The absorption rate and solubility of carbon dioxide (CO2 ) into 35 wt% aqueous potassium carbonate (K2 CO3 ) solution in the presence of different promoters were evaluated experimentally. A vapor–liquid equilibrium (VLE) apparatus was used to measure the equilibrium partial pressure of CO2 and CO2 partial pressure changes with time in CO2 partial pressures ranging from 0 to 50 kPa (low partial pressures) and at temperature 313.15 K. The activators considered are Piperazine (PZ), 2-(1-piperazinyl)-ethylamine (PZEA), Monoethanolamine (MEA), Tetraethylenepentamine (TEPA) and Boric acid (BA). Different molar ratios of the activator to K2 CO3 (0.25, 0.66 and 1.5) at constant total blend concentration of 2.5 mol dm −3 (M) were investigated to find the optimal molar ratio. Among studied promoters, the highest absorption rate and CO2 solubility was achieved with the TEPA + K2 CO3 solution with molar ratios of 0.66 and 1.5 respectively. As an overall conclusion, TEPA + K2 CO3 solution could be a potential candidate for CO2 capture.